Preparation method of wollastonite and anorthite multiphase ceramic green body with uneven surface

By using specific proportions of mineral raw material ingredients and high-temperature firing technology, a composite ceramic body of permeate and calcium feldspar was prepared, which solved the problems of surface unevenness and performance, and achieved low water absorption and high flexural strength. The effect is suitable for imitation stone and anti-slip road applications.

CN119118632APending Publication Date: 2024-12-13SHANDONG UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411299796.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

It is difficult to effectively prepare architectural ceramic materials with uneven surfaces in the prior art, and it is difficult for conventional methods to take into account the properties of low water absorption and high flexural strength during the firing process.

Method used

Mineral raw materials such as clay, sodium tripolyphosphate, kaolin, potassium feldspar, quartz, dolomite, wollastonite, barium carbonate and zinc oxide are prepared in a specific proportion. After ball milling and drying, they are formed using 200 MPa, and then in horse The furnace is gradually heated to 1170°C and fired to form a composite ceramic body of permeate and calcium feldspar. The reaction of dolomite and wollastonite is used to generate glass phases and crystalline phases, achieving the effect of uneven surfaces.

Benefits of technology

The surface of the prepared permeate and calcium feldspar complex ceramic body has significant uneven effect, low water absorption rate, high flexural strength, suitable for imitation stone materials and anti-slip road surfaces, and is simple in process, low in cost, and fast compatibility. Fire-making technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a preparation method of a wollastonite and anorthite multiphase ceramic green body with an uneven surface, and belongs to the technical field of architectural ceramics. The preparation method comprises the following steps: preparing pottery clay, sodium tripolyphosphate, kaolin, potassium feldspar, quartz, dolomite, wollastonite, barium carbonate and zinc oxide according to a mass ratio, adding water, carrying out ball milling in a rapid ball mill, drying the slurry, manually manufacturing material particles, sieving, taking the material particles between a 20-mesh sieve and a 40-mesh sieve or between the 40-mesh sieve and an 80-mesh sieve, and uniformly mixing the materials; and after compression molding, preparing in a muffle furnace to obtain a brushstone and anorthite multiphase ceramic green body with an uneven surface. The brushstone and anorthite multiphase ceramic green body is low in water absorption and high in strength, can be used for stone-like materials to achieve the uneven effect, and can also be used as an anti-slip walking pavement material to be applied to the travel field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a method for preparing a louverite and anorthite composite ceramic body with an uneven surface, belonging to the technical field of building ceramics. Background Art

[0002] With the improvement of living standards, people have higher and higher requirements for living environment and outdoor ground travel environment, as well as higher and higher requirements for decoration, finishing materials and pavement materials. Architectural ceramic decoration and finishing materials have low water absorption and good decorative performance, and their application in the fields of decoration, renovation and walking environment has received widespread attention. Conventional architectural ceramics have a flat and smooth surface and good decorative effect, but in applications such as imitating the concave and convex texture of stone, improving anti-slip effects, and decorative and finishing materials need to purposefully design an uneven structure on their surface. Common technical solutions include using molds with concave and convex surfaces for pressing, laser or mechanical polishing, and using the difference in the hydrophilic and hydrophobic properties of the glaze during the glazing process to achieve glaze sinking.

[0003] Chinese invention patent CN201910915321.7 reports a technical solution for controlling the effect through the concave and convex surface of the mold cavity and then realizing the uneven surface of the green body after pressing, that is, using a three-dimensional scanner to scan the texture of the natural stone surface, and after scanning, using a laser engraving machine to engrave the scanned natural stone surface texture on at least one cavity surface of the pressing mold. Chinese invention patent CN201610852429.2 reports that linear concave textures are formed on the surface of the green body by screen printing, and imitation marble tiles with concave effects are prepared. Chinese invention patent CN201911243016.4 reports a method of using a protective film and assisting sandblasting engraving, that is, a protective film is attached to the surface of the ceramic plate, the edge of the specified pattern is engraved on the protective film, the protective film of the part to be engraved is removed and the engraved surface is sandblasted, and the remaining protective film is removed and then the entire surface of the ceramic plate is sandblasted, cleaned, dried and coated with nitro lacquer to form an uneven shape. Chinese invention patent CN202111366055.0 reports a technical solution of first applying a base glaze on the surface of a ceramic tile green body, and then applying glaze-draining ink to achieve a surface concave-convex texture pattern, that is, applying a base glaze on the ceramic tile green body, then printing ink with a glaze-draining function in the concave area and the concave transition area of ​​the texture pattern, and then applying an intermediate glaze. By utilizing the characteristics that the glaze-draining ink is incompatible with the intermediate glaze, the part where the glaze-draining ink is printed repels the intermediate glaze to achieve a concave area, and the other areas are convex and concave-convex transition areas, and then applying a gloss glaze and a top glaze, and finally drying and firing to obtain a ceramic tile with an uneven corrugated texture. Chinese invention patent CN201610641042.2 reports a technical solution of applying a binder on the surface of a green body to achieve a concave-convex texture, that is, applying frit particles on the surface of the green body to which the binder is applied, blowing away the unbonded frit particles after drying, and finally firing to obtain a ceramic tile with a concave-convex texture on the surface. It can be seen that there is no reported technical solution of first preparing materials of specific components, then preparing particles of specific particle size, pressing and forming green bodies with smooth surfaces, and finally utilizing the interaction between materials during the firing process to achieve the uneven effect on the surface of the ceramic body. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a composite ceramic body of linalite and anorthite with an uneven surface, which is characterized by comprising the following steps: (1) Ingredients are prepared according to the mass ratio: 3.75% clay, 0.38% sodium tripolyphosphate, 32.25% kaolin, 39.75% potassium feldspar, 10.5% quartz, 45% dolomite, 4.5% wollastonite, 2.25% barium carbonate, and 1.88% zinc oxide. The mass percentages of the materials are 2.67% clay, 0.27% sodium tripolyphosphate, 22.99% kaolin, 28.34% potassium feldspar, 7.49% quartz, 32.08% dolomite, 3.21% wollastonite, 1.60% barium carbonate, 1.34% zinc oxide, add water to make the mass ratio of material to water 100:80, in a fast ball mill, after ball milling for 10 minutes, dry the slurry at 120°C, manually make particles and sieve, take the particles between 20 mesh and 40 mesh or between 40 mesh and 80 mesh, record as -20+40 mesh or -40+80 mesh particles; (2) placing the pellets obtained in step (1) into a mold and molding them at 200 MPa to obtain a ceramic green body; (3) The ceramic green body obtained in step (2) is placed in a muffle furnace, and the temperature is increased from room temperature to 700°C at a heating rate of 7°C per minute, and then increased to 1000°C at a heating rate of 5°C per minute, and then increased to 1170°C at a heating rate of 5°C per minute. Finally, the green body is kept at 1170°C for 15 minutes and then cooled in the furnace, thereby obtaining a composite ceramic green body of calcite and anorthite with an uneven surface.

[0005] Among them, the particle size of the building ceramic body obtained by step (1) has a significant effect on the surface unevenness effect. When the particles between 20 mesh and 40 mesh or between 20 mesh and 40 mesh are taken as -20+40 mesh or -40+80 mesh, respectively, the surface of the diopside and anorthite composite ceramic body obtained by steps (2) and (3) has an uneven effect, low water absorption rate and high flexural strength. During the firing process, dolomite and wollastonite provide CaO, MgO and SiO2 reaction elements between the materials, and synergistically react with other materials during the melting process to promote the formation of diopside (CaMg(Si2O6)) and anorthite (CaAl2Si2O8) phases in the glass phase, forming an uneven effect. At the same time, the molten glass phase can also ensure the densification sintering process of the ceramic, ensuring the effect of low water absorption rate and high flexural strength. When the pellets above the 20-mesh sieve are taken, the surface roughness is the most significant, but the water absorption rate and flexural strength performance are poor. When the pellets below the 80-mesh sieve are taken, the surface roughness is the smallest, but the porosity is high and the strength performance is not good.

[0006] The beneficial effects of the present invention are: 1. The main raw materials used in this process are common mineral raw materials, which have low cost, simple process, short high-temperature firing time, and high compatibility with the roller kiln rapid firing technology of building ceramics; 2. The surface of the composite ceramic body of calcite and calcium feldspar prepared by this process is uneven, which can be used to imitate stone materials to achieve an uneven effect, and can also be used as an anti-slip walking pavement material in the field of travel; 3. The glass phase of the calcite and calcium feldspar composite ceramic body prepared by the process method contains calcite and calcium feldspar composite crystalline phases. The presence of the glass phase can ensure that the pore connectivity in the body of the body is low and the water absorption rate is low. The presence of the crystalline phase can provide an effective strengthening and deflection mechanism for bearing higher loads and for the expansion of cracks, thereby achieving a high flexural strength effect. It can be used in application scenarios with high loads and long service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Attached Figure 1 This is the X-ray diffraction XRD spectrum of the wollastonite and anorthite composite ceramic body with an uneven surface prepared in Example 1.

[0008] Attached Figure 2 This is a scanning electron microscope (SEM) photograph of the pulvinite and anorthite composite ceramic body with an uneven surface prepared in Example 1.

[0009] Attached Figure 3 This is a scanning electron microscope (SEM) photograph of the pulvinite and anorthite composite ceramic body with an uneven surface prepared in Example 1.

[0010] Attached Figure 4 This is an optical microscope photograph of the wollastonite and anorthite composite ceramic body with an uneven surface prepared in Example 1.

[0011] Attached Figure 5 This is the X-ray diffraction XRD spectrum of the wollastonite and anorthite composite ceramic body with an uneven surface prepared in Example 2.

[0012] Attached Figure 6 This is a scanning electron microscope (SEM) photograph of the pulvinite and anorthite composite ceramic body with an uneven surface prepared in Example 2.

[0013] Attached Figure 7 This is a scanning electron microscope (SEM) photograph of the pulvinite and anorthite composite ceramic body with an uneven surface prepared in Example 2.

[0014] Attached Figure 8 This is an optical microscope photograph of the wollastonite and anorthite composite ceramic body with an uneven surface prepared in Example 2.

[0015] Attached Fig. 9The X-ray diffraction (XRD) spectrum of the wollastonite and anorthite composite ceramic body with an uneven surface prepared in Comparative Example 1 is shown.

[0016] Attached Fig.10 This is an optical microscope photograph of the wollastonite and anorthite composite ceramic body with an uneven surface prepared in Comparative Example 1.

[0017] Attached Fig.11 The X-ray diffraction (XRD) spectrum of the wollastonite and anorthite composite ceramic body with an uneven surface prepared in Comparative Example 2 is shown.

[0018] Attached Fig.12 This is an optical microscope photograph of the wollastonite and anorthite composite ceramic body with an uneven surface prepared in Comparative Example 2.

[0019] Attached Fig.13 The X-ray diffraction XRD spectrum of the architectural ceramic body prepared in Comparative Example 3 is shown.

[0020] Attached Fig.14 This is an optical microscope photograph of the architectural ceramic body prepared in Comparative Example 3.

[0021] Attached Fig.15 The X-ray diffraction (XRD) spectrum of the architectural ceramic body prepared in Comparative Example 4 is shown.

[0022] Attached Fig.16 This is a scanning electron microscope (SEM) photograph of the architectural ceramic body prepared in Comparative Example 4.

[0023] Attached Fig.17 This is a scanning electron microscope (SEM) photograph of the architectural ceramic body prepared in Comparative Example 4.

[0024] Attached Fig.18 This is an optical microscope photograph of the architectural ceramic body prepared in Comparative Example 4.

[0025] Attached Fig.19 This is the X-ray diffraction XRD spectrum of the architectural ceramic body prepared in Comparative Example 5.

[0026] Attached Fig. 20 This is a scanning electron microscope (SEM) photograph of the architectural ceramic body prepared in Comparative Example 5.

[0027] Attached Fig.21 This is a scanning electron microscope (SEM) photograph of the architectural ceramic body prepared in Comparative Example 5.

[0028] Attached Fig. 22 This is an optical microscope photograph of the architectural ceramic body prepared in Comparative Example 5.

[0029] Attached Fig.23This is the X-ray diffraction XRD spectrum of the architectural ceramic body prepared in Comparative Example 6.

[0030] Attached Fig.24 This is an optical microscope photograph of the architectural ceramic body prepared in Comparative Example 6. DETAILED DESCRIPTION Example 1

[0031] (1) The ingredients are prepared according to the mass ratio: 3.75% clay, 0.38% sodium tripolyphosphate, 32.25% kaolin, 39.75% potassium feldspar, 10.5% quartz, 45% dolomite, 4.5% wollastonite, 2.25% barium carbonate, and 1.88% zinc oxide, that is, the mass percentages of the materials are 2.67% clay, 0.27% sodium tripolyphosphate, 22.99% kaolin, 28.34% potassium feldspar, 7.49% quartz, 32.08% dolomite, 3.21% wollastonite, 1.60% barium carbonate, and 1.34% zinc oxide, respectively. Water is added so that the mass ratio of the materials to the water is 100:80. After ball milling for 10 minutes in a rapid ball mill, the slurry is dried at 120° C. The granules are manually prepared and sieved. The granules between the 20-mesh sieve and the 40-mesh sieve are taken and recorded as -20+40-mesh granules. (2) placing the pellets obtained in step (1) into a mold and molding them at 200 MPa to obtain a ceramic green body; (3) The ceramic green body obtained in step (2) is placed in a muffle furnace, and the temperature is increased from room temperature to 700°C at a heating rate of 7°C per minute, and then increased to 1000°C at a heating rate of 5°C per minute, and then increased to 1170°C at a heating rate of 5°C per minute. Finally, the green body is kept at 1170°C for 15 minutes and then cooled in the furnace, thereby obtaining a composite ceramic green body of calcite and anorthite with an uneven surface.

[0032] The sintered wollastonite and anorthite composite ceramic body with an uneven surface obtained in step (3) has a linear shrinkage of 11.72%, a mass loss of 16.05%, a density of 2.33 g / cm3, an apparent porosity of 1.47%, and a water absorption of 0.63%. Figure 1 As shown in the X-ray diffraction (XRD) pattern of the sample, the main crystalline phase corresponding to the stronger diffraction peak is diopside (JCPDS No. 86-0932) phase, and the diffraction peaks of anorthite (JCPDS No. 41-1486) appear near angles such as 2θ=21.96º, 23.59º, 25.68º, 35.16º, 37.89º, 44.53º and 57.56º. Figure 2 , 3As shown in Figure 4, in the scanning electron microscope SEM and optical photos, the ceramic surface shows obvious uneven morphology, and the glass phase is embedded with needle-shaped crystal phases. The average flexural strength tested by the three-point bending test method is 30.57 MPa, and the standard deviation is 4.08 MPa. Example 2

[0033] (1) Ingredients are prepared according to the mass ratio: 3.75% clay, 0.38% sodium tripolyphosphate, 32.25% kaolin, 39.75% potassium feldspar, 10.5% quartz, 45% dolomite, 4.5% wollastonite, 2.25% barium carbonate, and 1.88% zinc oxide, that is, the mass percentages of the materials are 2.67% clay, 0.27% sodium tripolyphosphate, 22.99% kaolin, 28.34% potassium feldspar, 7.49% quartz, 32.08% dolomite, 3.21% wollastonite, 1.60% barium carbonate, and 1.34% zinc oxide, respectively. Water is added so that the mass ratio of the materials to the water is 100:80. After ball milling for 10 minutes in a rapid ball mill, the slurry is dried at 120° C. Granules are manually prepared and sieved. Granules between the 40-mesh sieve and the 80-mesh sieve are taken and recorded as -40+80-mesh granules. (2) placing the pellets obtained in step (1) into a mold and molding them at 200 MPa to obtain a ceramic green body; (3) placing the pulvinite and anorthite composite ceramic body with an uneven surface obtained in step (2) in a muffle furnace, heating the temperature from room temperature to 700°C at a heating rate of 7°C per minute, then heating the temperature to 1000°C at a heating rate of 5°C per minute, then heating the temperature to 1170°C at a heating rate of 5°C per minute, and finally keeping the temperature at 1170°C for 15 minutes and then cooling the body with the furnace to obtain a pulvinite and anorthite composite ceramic body with an uneven surface.

[0034] The low water absorption reinforced architectural ceramic body obtained in step (3) has a linear shrinkage of 13.37%, a mass loss of 17.22%, a density of 2.60 g / cm3, an apparent porosity of 0.56%, and a water absorption of 0.22%. Figure 5 As shown in the X-ray diffraction (XRD) pattern of the sample, the main crystalline phase corresponding to the stronger diffraction peak is diopside (JCPDS No. 86-0932) phase, and the diffraction peaks of anorthite (JCPDS No. 41-1486) appear near the angles of 2θ=22.00º, 22.72º, 23.57º, 25.60º, 33.60º, 36.85º and 52.57º. Figure 6 , 7As shown in Figure 8, in the scanning electron microscope SEM photos and optical microscope photos, the ceramic surface clearly shows uneven morphology, and the glass phase is embedded with needle-shaped crystal phases. The average flexural strength tested by the three-point bending test method is 52.23 MPa, and the standard deviation is 12.76 MPa.

[0035] Comparative Example 1 (1) The ingredients are prepared according to the mass ratio: 3.75% clay, 0.38% sodium tripolyphosphate, 32.25% kaolin, 39.75% potassium feldspar, 10.5% quartz, 45% dolomite, 4.5% wollastonite, 2.25% barium carbonate, and 1.88% zinc oxide, that is, the mass percentages of the materials are 2.67% clay, 0.27% sodium tripolyphosphate, 22.99% kaolin, 28.34% potassium feldspar, 7.49% quartz, 32.08% dolomite, 3.21% wollastonite, 1.60% barium carbonate, and 1.34% zinc oxide, respectively. Water is added so that the mass ratio of the materials to the water is 100:80. After ball milling for 10 minutes in a rapid ball mill, the slurry is dried at 120° C. The granules are manually made and sieved. The granules on the 20-mesh sieve are taken and recorded as +20-mesh granules. (2) placing the pellets obtained in step (1) into a mold and molding them at 200 MPa to obtain a ceramic green body; (3) The ceramic green body obtained in step (2) is placed in a muffle furnace, and the temperature is increased from room temperature to 700°C at a heating rate of 7°C per minute, and then increased to 1000°C at a heating rate of 5°C per minute, and then increased to 1170°C at a heating rate of 5°C per minute. Finally, the green body is kept at 1170°C for 15 minutes and then cooled in the furnace, thereby obtaining a composite ceramic green body of calcite and anorthite with an uneven surface.

[0036] The sintered wollastonite and anorthite composite ceramic body with an uneven surface obtained in step (3) has a linear shrinkage of 13.69%, a mass loss of 15.42%, a density of 2.42 g / cm3, an apparent porosity of 2.57%, and a water absorption of 1.06%. Fig. 9 As shown in the X-ray diffraction (XRD) pattern of the sample, the main crystalline phase corresponding to the stronger diffraction peak is diopside (JCPDS No. 86-0932) phase, and the diffraction peaks of anorthite (JCPDS No. 41-1486) appear near the angles of 2θ=14.88º, 23.61º, 31.80º, 41.33º and 45.55º. Fig.10 As shown in the optical microscope photo, the ceramic surface shows a prominent uneven morphology. The flexural strength is 26.76 MPa as tested by the three-point bending test method.

[0037] Comparative Example 2 (1) Ingredients are prepared according to the mass ratio: 3.75% clay, 0.38% sodium tripolyphosphate, 32.25% kaolin, 39.75% potassium feldspar, 10.5% quartz, 45% dolomite, 4.5% wollastonite, 2.25% barium carbonate, and 1.88% zinc oxide, that is, the mass percentages of the materials are 2.67% clay, 0.27% sodium tripolyphosphate, 22.99% kaolin, 28.34% potassium feldspar, 7.49% quartz, 32.08% dolomite, 3.21% wollastonite, 1.60% barium carbonate, and 1.34% zinc oxide, respectively. Water is added so that the mass ratio of the materials to the water is 100:80. After ball milling in a fast ball mill for 10 minutes, the slurry is dried at 120° C. Granules are manually prepared and sieved. The granules under the 80-mesh sieve are taken and recorded as -80-mesh granules. (2) placing the pellets obtained in step (1) into a mold and molding them at 200 MPa to obtain a ceramic green body; (3) The ceramic green body obtained in step (2) is placed in a muffle furnace, and the temperature is increased from room temperature to 700°C at a heating rate of 7°C per minute, and then increased to 1000°C at a heating rate of 5°C per minute, and then increased to 1170°C at a heating rate of 5°C per minute. Finally, the green body is kept at 1170°C for 15 minutes and then cooled in the furnace, thereby obtaining a composite ceramic green body of calcite and anorthite with an uneven surface.

[0038] The sintered wollastonite and anorthite composite ceramic body with an uneven surface obtained in step (3) has a linear shrinkage of 13.34%, a mass loss of 17.10%, a density of 2.20 g / cm3, an apparent porosity of 14.87%, and a water absorption of 6.76%. Fig.11 As shown in the X-ray diffraction XRD pattern of the sample, the main crystalline phase corresponding to the stronger diffraction peak is diopside (JCPDS No. 86-0932) phase, and the diffraction peaks of anorthite (JCPDS No. 41-1486) appear near the angles of 2θ=22.00º, 22.77º, 23.66º, 25.65º, 27.88º, 33.73º, 35.19º, 36.89º, and 57.57º. Fig.12 As shown in the optical microscope photo, the ceramic surface does not show the uneven morphology in particular detail. The flexural strength was tested by the three-point bending test method and was 34.65 MPa.

[0039] Comparative Example 3 (1) Take the powder used for molding after spray granulation and aging by a certain scientific and technological ceramics company, add water to make the mass ratio of material to water 100:80, and mill it in a fast ball mill for 10 minutes. Dry the slurry at 120°C, make granules manually and sieve them, and take the granules on the 20-mesh sieve, which are recorded as +20-mesh granules; (2) placing the pellets obtained in step (1) into a mold and molding them at 200 MPa to obtain a ceramic green body; (3) The ceramic green body obtained in step (2) is placed in a muffle furnace, and the temperature is increased from room temperature to 700°C at a heating rate of 7°C per minute, and then increased to 1000°C at a heating rate of 5°C per minute, and then increased to 1170°C at a heating rate of 5°C per minute. Finally, the green body is kept at 1170°C for 15 minutes and then cooled in the furnace to obtain a building ceramic green body.

[0040] The architectural ceramic body obtained in step (3) has a linear shrinkage of 11.03%, a mass loss of 3.11%, a density of 2.42 g / cm3, an apparent porosity of 3.95%, and a water absorption of 1.63%. Fig.13 As shown in the X-ray diffraction XRD pattern of the sample, the main crystalline phase corresponding to the stronger diffraction peak is the quartz (JCPDS No. 65-0466) phase, and the diffraction peaks of mullite (JCPDS No. 79-1455) appear near the angles of 2θ=16.42º, 22.85º, 35.24º, 40.84º, 48.28º, 53.93º, 60.75º, 61.53º, 64.44º, 65.45º and 69.46º. As shown in the attached figure Fig.14 As shown in the optical microscope photo, the ceramic surface shows almost no uneven morphology. The flexural strength was tested by the three-point bending test method and was 17.48 MPa.

[0041] Comparative Example 4 (1) Take the powder used for molding after spray granulation and aging by a certain scientific and technological ceramics company, add water to make the mass ratio of material to water 100:80, and mill it in a fast ball mill for 10 minutes. Dry the slurry at 120°C, make granules manually and sieve them, and take the granules between the 20-mesh sieve and the 40-mesh sieve, which are recorded as -20+40-mesh granules; (2) placing the pellets obtained in step (1) into a mold and molding them at 200 MPa to obtain a ceramic green body; (3) The ceramic green body obtained in step (2) is placed in a muffle furnace, and the temperature is increased from room temperature to 700°C at a heating rate of 7°C per minute, and then increased to 1000°C at a heating rate of 5°C per minute, and then increased to 1170°C at a heating rate of 5°C per minute. Finally, the green body is kept at 1170°C for 15 minutes and then cooled in the furnace to obtain a building ceramic green body.

[0042] The reinforced architectural ceramic body obtained in step (3) has a linear shrinkage of 11.67%, a mass loss of 3.17%, a density of 2.34 g / cm3, an apparent porosity of 4.88%, and a water absorption of 2.08%. Fig.15 As shown in the X-ray diffraction XRD pattern of the sample, the main crystalline phase corresponding to the stronger diffraction peak is the quartz (JCPDS No. 65-0466) phase, and the diffraction peaks of mullite (JCPDS No. 79-1455) appear near the angles of 2θ=16.55º, 33.26º, 35.42º, 40.92º, 53.46º, 60.79º, 64.60º and 66.54º. Fig.16 , 17 As shown in Figures 18, in the scanning electron microscope SEM photos and optical microscope photos, the ceramic surface shows a flat morphology without obvious uneven features, and a small amount of crystalline phase is embedded in the glass phase. The flexural strength tested by the three-point bending test method is 19.93MPa.

[0043] Comparative Example 5 (1) Take the powder used for molding after spray granulation and aging by a certain scientific and technological ceramics company, add water to make the mass ratio of material to water 100:80, and mill it in a fast ball mill for 10 minutes. Dry the slurry at 120°C, make granules manually and sieve them, and take the granules between the 40-mesh sieve and the 80-mesh sieve, which are recorded as -40+80-mesh granules; (2) placing the pellets obtained in step (1) into a mold and molding them at 200 MPa to obtain a ceramic green body; (3) The ceramic green body obtained in step (2) is placed in a muffle furnace, and the temperature is increased from room temperature to 700°C at a heating rate of 7°C per minute, and then increased to 1000°C at a heating rate of 5°C per minute, and then increased to 1170°C at a heating rate of 5°C per minute. Finally, the green body is kept at 1170°C for 15 minutes and then cooled in the furnace to obtain a building ceramic green body.

[0044] The architectural ceramic body obtained in step (3) has a linear shrinkage of 12.15%, a mass loss of 3.19%, a density of 2.37 g / cm3, an apparent porosity of 1.40%, and a water absorption of 0.59%. Fig.19 As shown in the X-ray diffraction XRD pattern of the sample, the main crystalline phase corresponding to the stronger diffraction peak is the quartz (JCPDS No. 65-0466) phase, and the diffraction peaks of mullite (JCPDS No. 79-1455) appear near the angles of 2θ=16.45º, 26.05º, 33.31º, 35.28º, 40.89º, 60.74º, 61.58º, 64.67º, 65.37º and 66.60º. As shown in the attached figure Fig. 20 , 21 As shown in the scanning electron microscope (SEM) and optical microscope images, the ceramic surface exhibits a flat morphology (e.g. Fig. 20 As shown on the left, there is no obvious uneven feature, and a small amount of crystalline phase is embedded in the glass phase. The flexural strength is 28.91 MPa tested by the three-point bending test method.

[0045] Comparative Example 6 (1) Take the powder used for molding after spray granulation and aging by a certain scientific and technological ceramics company, add water to make the mass ratio of material to water 100:80, and mill it in a fast ball mill for 10 minutes. Dry the slurry at 120°C, make granules manually and sieve them. Take the granules under the 80-mesh sieve and record them as -80-mesh granules; (2) placing the pellets obtained in step (1) into a mold and molding them at 200 MPa to obtain a ceramic green body; (3) The ceramic green body obtained in step (2) is placed in a muffle furnace, and the temperature is increased from room temperature to 700°C at a heating rate of 7°C per minute, and then increased to 1000°C at a heating rate of 5°C per minute, and then increased to 1170°C at a heating rate of 5°C per minute. Finally, the green body is kept at 1170°C for 15 minutes and then cooled in the furnace to obtain a building ceramic green body.

[0046] The architectural ceramic body obtained in step (3) has a linear shrinkage of 11.50%, a mass loss of 3.33%, a density of 2.36 g / cm3, an apparent porosity of 2.65%, and a water absorption of 1.13%. Fig.23 As shown in the X-ray diffraction XRD pattern of the sample, the main crystalline phase corresponding to the stronger diffraction peak is the quartz (JCPDS No. 65-0466) phase, and the diffraction peaks of mullite (JCPDS No. 79-1455) appear near the angles of 2θ=16.47º, 33.28º, 35.29º, 40.91º, 57.84º, 58.84º, 60.78º and 64.66º. Fig.24As shown in the optical microscope photo, the ceramic surface shows almost no uneven morphology. The flexural strength was tested by the three-point bending test method and was 22.79 MPa.

Claims

1. A method for preparing a composite ceramic body of linalite and anorthite with an uneven surface, Features The following steps are involved: (1) Ingredients are prepared according to the mass ratio: 3.75% clay, 0.38% sodium tripolyphosphate, 32.25% kaolin, 39.75% potassium feldspar, 10.5% quartz, 45% dolomite, 4.5% wollastonite, 2.25% barium carbonate, and 1.88% zinc oxide. The mass percentages of the materials are 2.67% clay, 0.27% sodium tripolyphosphate, 22.99% kaolin, 28.34% potassium feldspar, 7.49% quartz, 32.08% dolomite, 3.21% wollastonite, 1.60% barium carbonate, 1.34% zinc oxide, add water to make the mass ratio of material to water 100:80, in a fast ball mill, after ball milling for 10 minutes, dry the slurry at 120°C, manually make particles and sieve, take the particles between 20 mesh and 40 mesh or between 40 mesh and 80 mesh, record as -20+40 mesh or -40+80 mesh particles; (2) placing the pellets obtained in step (1) into a mold and molding them at 200 MPa to obtain a ceramic green body; (3) The ceramic green body obtained in step (2) is placed in a muffle furnace, and the temperature is increased from room temperature to 700°C at a heating rate of 7°C per minute, and then increased to 1000°C at a heating rate of 5°C per minute, and then increased to 1170°C at a heating rate of 5°C per minute. Finally, the green body is kept at 1170°C for 15 minutes and then cooled in the furnace, thereby obtaining a composite ceramic green body of calcite and anorthite with an uneven surface.

Citation Information

Patent Citations

  • Craft porcelain with raised particle effect on glaze surface and preparation method thereof

    CN110963781A

  • Soft ceramic tile with concave-convex textures and preparation method thereof

    CN116477922A

  • Preparation method of low-water-absorption composite crystal phase reinforced building ceramic green body containing brushstone and anorthite

    CN118652108A

  • Ultra low thermal expansion transparent glass-ceramics

    EP1516863A1